Corporate profitability in Ireland: overview and determinants - Nugent, Jim (Statistical and Social Inquiry Society of Ireland, 1999)
The study of profits is important not only because of the information it provides about the health of the economy in any given year, but also because profits are a key determinant of growth and employment in the medium-term. Changes in profitability are an important contributor to economic progress via the influence profits have on the investment and savings decisions of companies. This is because a rise in profits improves the cash-flow position of companies and offers greater flexibility in the source of finance for corporate investment (i.e. through retained earnings). Easier access to finance facilitates greater investment which boosts productivity, productive capacity, competitiveness and employment. This paper has a number of objectives. Firstly, it presents an overview of recent trends in profitability in Ireland, both at a manufacturing/sectoral level as well as at a broader macroeconomic level. Secondly, the paper tries to determine, in an impressionistic way, the range of likely factors (such as exchange rates and the degree of monopoly power) which influence movements in profitability. A third objective is to briefly review the capital structure of Irish industry and the implications for the financial well-being of the corporate sector. Finally, the paper explores the relation between profits/retentions with investment and employment, which is a key motivation for the study of profits in the first place.
Read before the Society, 26 November 1998
Keywords: Profits - Ireland; 314.15